1978
DOI: 10.1111/j.1365-246x.1978.tb06755.x
|View full text |Cite
|
Sign up to set email alerts
|

LISPB -- IV. Crustal structure of Northern Britain

Abstract: This paper presents those results from the 1974 Lithospheric Seismic Profde in Britain (LISPB) which relate to the compressional velocity structure of the crust and uppermost mantle beneath Northern Britain. A combination of interpretation techniques suitable for modelling laterally inhomogeneous media, including twodimensional ray-tracing and timeterm analysis, has resulted in a detailed seismic cross-section across the Caledonian orogenic belt. The main features of this section are a possible horizontal disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(84 citation statements)
references
References 11 publications
6
78
0
Order By: Relevance
“…Interpreted depths of the Moho across Scotland range from 36 km in the Midland Valley to 22 km off Cape Wrath (Trewin, 2002), and this is also consistent with the results of the LISPB experiments in Scotland (e.g. Bamford et al, 1978;Barton, 1992). The sharp increase in crustal thickness observed by Di Leo et al (2009) west of the Moine thrust is not observed in our results.…”
Section: Discussionsupporting
confidence: 82%
“…Interpreted depths of the Moho across Scotland range from 36 km in the Midland Valley to 22 km off Cape Wrath (Trewin, 2002), and this is also consistent with the results of the LISPB experiments in Scotland (e.g. Bamford et al, 1978;Barton, 1992). The sharp increase in crustal thickness observed by Di Leo et al (2009) west of the Moine thrust is not observed in our results.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the deep Grampian crust could contain Lewisian, Grenvillian and Caledonian rocks. There may also be a rock layer below the Lewisian, with a density consistent with granulite-facies intermediate to felsic rocks (Bamford et al, 1978). Evidently, the crust below the Grampian terrane is potentially highly complex.…”
Section: Potential Magma Sources In the Crust And Mantlementioning
confidence: 99%
“…This level of detail is not reached by the tomography discussed here and so it is reasonable to compare directly with the 1978 model for clarity. Figure 11 shows the location of the LISPB line and a copy of the line drawing by (Bamford et al, 1978). A profile through the 3-D tomography model is shown for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen shots of between two and six tons of explosive were recorded by up to 40 stations along this line. One of the products of this experiment was a 2-D velocity profile along the line (Bamford et al, 1978), that has formed the basis of the velocity model used for earthquake location in Scotland ever since. (Barton, 1992) refined the 1978 LISPB model but her model remains broadly similar with the most obvious difference the addition of intermediate layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation